Interprofessional education: collaborative team work among undergraduate medical students - Shumaila Rafi (Journal of the Pakistan Medical Association, 2023)
Madam, The last decade has been a global shift towards collaborative learning and practice. A Joint Commission Report noticed that 80% of all medical errors were due to miscommunications during patient handoffs, with 44% occurring in inpatient settings1. Learning Together to Work Together for Health is the essential guide for the working of Interprofessional Education (IPE), the idea presented by WHO and is defined as an experience that “occurs when students from two or more professions learn about, from, and with each other to enable effective collaboration and improve outcomes”2. The core competencies for IPE include collaborative teamwork, communication skills, ethical practice, roles and responsibilities, and conflict resolution2. IPE expects to improve the knowledge, skills, and attitudes towards collaboration to enhance their future clinical practice. Pakistan is a developing country that is strengthening IPE. The Karachi Medical and Dental College launched a training program on research methodology focusing on the principles of IPE to improve primary care delivery2. The Dental Hygiene Program at Aga Khan University is also an example of IPE improving patient healthcare3. These deficiencies can be overcome by vertically and horizontally integrating IPE in the curriculum. The absence of a formal team-based care programme deprives most students from learning about professional roles. This warrants a need to focus on learning approaches that can be used in undergraduate curricula and thereby create and foster a collaborative learning environment. Case-based learning and team-based learning are valuable approaches resulting in experiential learning and reflection. Simulations allow students to practice and improve their communication and collaboration among medical students. E-learning is worthwhile for enlightening their understanding and cognizance of further profession’s duties and authorities, which is unique to the leading competencies of IPE4. The logistics of setting up IPE activities may be more challenging. The leadership confrontation such as lack of management between the faculties and lack of support by organization, curriculum challenges like IPE courses designing, teaching challenges, such as shortage of faculty members training, skills and competence in interprofessional and resistance to transformation i.e. dearth of resources are the main challenges for the institutions5. The institutions should engage in policies in the best strategies to implement interprofessional education. Hierarchical heads and policymakers need to put forth an effort to advance IPE so that different professions can benefit from each other more easily.